2005
DOI: 10.1063/1.2051806
|View full text |Cite
|
Sign up to set email alerts
|

Microwave attenuation of multiwalled carbon nanotube-fused silica composites

Abstract: Multiwalled carbon nanotubes (MWCNTs) were used to convert radome materials to microwave absorbing materials. Dense MWCNT-fused silica composites were prepared by hot-pressing technique. The composites exhibit high complex permittivities at X-band frequencies, depending on the content of MWCNTs. The value of the loss tangent increases three orders over pure fused silica only by incorporating 2.5vol% MWCNTs into the composites. The average magnitude of microwave transmission reaches −33dB at 11–12GHz in the 10v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
95
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(101 citation statements)
references
References 24 publications
6
95
0
Order By: Relevance
“…This is clearly shown in Figure 1(b). In Figure 1(a) and (b), the values of ε r ' and σ reported for the CNT composites [3][4][5][6][7][8][9] are plotted, although they were not measured at 5.8 or 60 GHz. The reported CNT composites seemed to be unsuitable for the single-layer absorbers with sufficient absorption coefficients at both frequencies.…”
Section: Materials Designmentioning
confidence: 99%
See 1 more Smart Citation
“…This is clearly shown in Figure 1(b). In Figure 1(a) and (b), the values of ε r ' and σ reported for the CNT composites [3][4][5][6][7][8][9] are plotted, although they were not measured at 5.8 or 60 GHz. The reported CNT composites seemed to be unsuitable for the single-layer absorbers with sufficient absorption coefficients at both frequencies.…”
Section: Materials Designmentioning
confidence: 99%
“…In the design of commonly used multilayer EM absorbers with metal backplanes, the thickness, permittivity, and/or conductivity of each layer must be adjusted to achieve high absorbance at a target frequency [2]. CNT composites are effective to achieve wide ranges of permittivity and conductivity [3][4][5][6][7][8][9] and to widen design flexibility of EM absorbers. A high conductivity of more than 10 3 S/m has been reported for both singlewalled (SW) [10] and multi-walled (MW) [11] CNT composites, while a large real permittivity of 200 at 18 GHz has been observed for MWCNT/cellulose composite paper [12].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a growing number of alternative lightweight materials with high EMI SE at high frequencies have been developed to replace or supplement typical metals used in EMI shielding. [7][8][9][10] In recent years, electrically conductive ceramic materials or their composites, such as Ti 3 SiC 2 or Ti 3 SiC 2 /Al 2 O 3 composites, 11 and others 12 have been examined for use in EMI shielding, and a high EMI SE of 35 dB to 54 dB in the frequency range of 8.2 GHz to 18 GHz can be obtained. In particular, carbon materials, such as carbon black, 13 graphite flakes, 14 carbon fiber, 15 and carbon nanotubes (CNTs) 16 have been explored as possible lightweight electromagnetic shielding and absorbing materials.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Mishra et al [10] found that the phenolic resin sheet consisting of multiphase such as EG, γ-Fe 2 O 3 , silica and carbon fiber exhibits enhanced shielding effectiveness (from 18.77 to 55.40 dB) in the frequency range of 8.2 -12.4 GHz (X-band). However, Xiang et al [12] used silica particles for fabricating MWCNT-fused silica composites for electromagnetic interference shielding.…”
mentioning
confidence: 99%